Large anterior abdominal wall fibrosarcoma in a known case of recurrent dermatofibrosarcoma protuberans - Kamini, Snigdha; Jain, Sunil Kumar; Bajwa, Jaspreet; Ahamad, M. Nafees; Prasad, Sumit Kumar; Sharma, Shivam; Srinivas, Pradeep Mekha (International Surgery Journal, 2020)
Dermatofibrosarcoma protuberans is a rare soft tissue sarcoma of low to intermediate malignant potential. Incidence is estimated to be 0.8 to 4.5 cases per million persons per year. The tumor is highly aggressive locally and is known to recur. Punch biopsy or excisional biopsy (in case of small tumors) are diagnostic. Computer tomography (CT) and magnetic resonance imaging (MRI) are useful in determining the size and extent of the tumor’s treatment is primarily surgical, with a wide local excision with at 2 cm margin. However, local recurrence after apparently adequate surgical excision is common. Mohs micrographic surgery has been recommended as it enables maximum preservation of tissue. When surgery is insufficient, imatinib mesylate is shown as a safe and effective treatment in dermatofibrosarcoma protuberans (DFSP), especially in cases of locally advanced or metastatic disease. Here, we report a case of a giant fibrosarcoma on the anterior abdominal wall, measuring 27×18×9 cm, which occurred in a recurrent dermatofibrosarcoma protuberans. Diagnosis was done by histopathological examination (HPE) of the previously excised tumor and CT was done. The tumor was excised with a 3 cm margin and extensive reconstruction of the anterior abdominal wall defect was done using synthetic mesh, myocutaneous flaps and split skin grafting. Keeping in view the recurrent nature of our case, large tumor size, DFSP-fibrosarcomatous (FS) transformation and close negative margins in the HPE of the postoperative specimen, the patient was planned for adjuvant radiotherapy.